Determinants of the dividend payout policy of multinational companies in Bangladesh: Evidence from Dhaka stock exchange - Hossain, Tarik; Khalifa, Md. Miraz; Ahmmed, Raju (Financial Risk and Management Reviews, 2023)
This study tries to establish the important factors influencing the dividend payout policy of the Multinational Companies (MNCs) in Bangladesh in order to assist investors in making the best possible investment decisions. Data for this study was collected from several MNCs listed on the DSE from 2015 to 2021. The relationship between the dependent variable, Dividend Payout Ratio (DPR) and selected independent variables such as Return on Equity (ROE), Liquidity Ratio (LEQR), Leverage Ratio (LEVR), Firm Size (FS), Dividend Payout Ratio of Previous Year (PDPR), Corporate Tax Ratio (CTR) and Capital Adequacy Ratio (CAR) is evaluated using Pearson’s correlation and Ordinary Least Squares (OLS) regression models for data analysis and hypothesis testing. The regression analysis results showed a mixed result. The ROE and CTR are significantly related to DPR. Higher ROE and CTR emphasis a higher dividend for stock holders. The FS is significantly negatively related to DPR. Due to the costs associated with paying for the profits of substantial assets, large firms pay lower dividends. Other variables such as LEQR, LEVR, PDPR, CTR and CAR have no significant impact on the DPR. The investors and the concerned authorities can consider ROE, CTR and FS to forecast the future dividend for the MNCs in Bangladesh.